2022
DOI: 10.1017/s0022149x22000591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing forage legumes on the migration and survival in the pasture of gastrointestinal nematodes of sheep

Abstract: In order to identify types of forage that inhibit pasture contamination, an evaluation was performed of the effect of the forage legumes Trifolium repens (white clover), Trifolium pratense (red clover) and Lotus corniculatus (bird's-foot-trefoil) on the survival and migration of infective larvae (L3) of gastrointestinal nematodes (GIN) of sheep. An experimental area of 441 m2 was divided into four blocks, subdivided into areas of 1.20 × 1.20 in which the three forage legumes were separately overseeded. After g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The pasture infectivity seems greatly determined by rainfall with high L3 levels in autumn-winter that decreases towards summer [143]. Similar results were obtained in summer in a coastal area in southern Brazil [112,153]. Another rotational system, cited in Sweden, consisted of separate 2 ha-paddocks with a grazing period of approximately 20 weeks [163,164].…”
Section: Some Environmental and Grazing Management Effects On The Par...supporting
confidence: 57%
See 2 more Smart Citations
“…The pasture infectivity seems greatly determined by rainfall with high L3 levels in autumn-winter that decreases towards summer [143]. Similar results were obtained in summer in a coastal area in southern Brazil [112,153]. Another rotational system, cited in Sweden, consisted of separate 2 ha-paddocks with a grazing period of approximately 20 weeks [163,164].…”
Section: Some Environmental and Grazing Management Effects On The Par...supporting
confidence: 57%
“…Additionally, the forage and legume species may also influence the ingestion of L3 by animals, which offers a potential tool for reducing contact with the parasite. Garcia-Méndez, et al [153] compared the vertical and horizontal migration of L3 of gastrointestinal nematodes in sheep across three legume species: white clover (Trifolium repens), red clover (T. pratense), and bird's-foot-trefoil (Lotus corniculatus), finding that smaller numbers of L3 were recovered from the upper stratum of the third plant species. Others [154] showed that, depending on the season, the forage species may be either a limiting or facilitating factor of L3 vertical migration.…”
Section: Some Environmental and Grazing Management Effects On The Par...mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be addressed in future using a combination of small‐scale, short‐term studies investigating the effect of plant species on pasture larvae counts in the field and models capable of extrapolating such data to estimate landscape‐level exposure over longer time periods (e.g. Garcia‐Méndez et al, 2022 ; Rose et al, 2015 ). The effect of PC1 is consistent with high‐quality grazing areas being more heavily used by sheep and thus higher strongyle burdens in lambs.…”
Section: Discussionmentioning
confidence: 99%
“…As these plants have a higher protein concentration and often higher levels of trace elements than grass, it may be that some of their effect is nutritional. Also, plant structure may inhibit larval migration, reducing larval ingestion (Garcia‐Mendez and others 2022). These plants may be used in single species stands, to provide high quality, clean grazing for lambs to graze as part of a rotation, or at a particular time of year (eg, after weaning).…”
Section: New Developments In Non‐chemotherapeutic Controlmentioning
confidence: 99%